An immune responsive tumor microenvironment imprints into PBMCs and predicts outcome in advanced pancreatic cancer: lessons from the PREDICT trial - Lahusen, Anton; Lutz, Manfred P.; Fang, Rui; Kirchner, Martina; Albus, Sarah; Kluck, Klaus; Karthaus, Meinolf; Schwarzer, Andreas; Siegler, Gabriele; Kleger, Alexander; Ettrich, Thomas J.; Becher, Alexander; et al. (Molecular cancer, 2025)
Prognosis in advanced pancreatic ductal adenocarcinoma (aPDAC) is particularly poor, only few patients benefit from treatment, and there are few biomarkers. The PREDICT trial examined whether first-line time-to-treatment failure (TTF1) predicts second-line treatment failure (TTF2) in aPDAC patients but found no association. We hypothesized that the tumor immune microenvironment (TiME) could correlate with the outcome in this trial and assessed whether tissue features were reflected in peripheral blood.